All the President's Men - Carl Bernstein, , Bob Woodward (Simon Schuster, 2014)
This landmark book details all the events of the biggest political scandal in the history of this nation--Watergate. Woodward and Bernstein kept the headlines coming, delivering revelation after amazing revelation to a shocked public. Black-and-white photograph section.